Teacher strategies for reducing Mathematics anxiety among secondary school students in Tanzania - Jonas Kinanda; Florence Kyaruzi; Katherine Fulgence (African Journal of Teacher Education)
This study explored strategies that teachers use to reduce mathematics anxiety among students in secondary schools in Tanzania. The study employed a qualitative exploratory case study design whereby data were obtained from 18 mathematics teachers and 40 students by using interviews, focus group discussions, and field observation. The data were then analysed thematically using Braun and Clarke’s (2006) thematic analysis model. Different dominant factors that contribute to mathematics anxiety among students were found to be poor mathematics background, teachers’ aggressiveness as well as the nature of mathematics as a difficult subject. Also, it was found that teachers can use various strategies to reduce mathematics anxiety among students which include teachers’ self-control, the use of rewards and reinforcement, and engaging students in teaching. Although teachers play a crucial role in reducing students’ mathematics anxiety, it is recommended that conjoint efforts should be made by several educational stakeholders to overcome the problem.